Improving the Diagnosis of Ipsilateral Femoral Neck and Shaft Fractures: A New Imaging Protocol. (19th February 2020) - Rogers, Nathan B.; Hartline, Braden E.; Achor, Timothy S.; Kumaravel, Manickam; Gary, Joshua L.; Choo, Andrew M.; Routt, Milton L.; Munz, John W.; Warner, Stephen J.
Abstract : Background: Despite increased awareness of ipsilateral femoral neck fractures in patients with high-energy femoral shaft fractures and advanced imaging with thin-cut high-resolution computed tomography (CT), failure of diagnosis remains problematic. The purpose of the present study was to determine if the preoperative diagnosis of ipsilateral femoral neck fractures in patients with high-energy femoral shaft fractures can be improved with magnetic resonance imaging (MRI) compared with radiographic and CT imaging. Methods: In response to delayed diagnoses of femoral neck fractures despite thin-cut high-resolution CT, our institutional imaging protocol for acute, high-energy femoral shaft fractures was altered to include rapid limited-sequence MRI to evaluate for occult femoral neck fractures. All patients received standard radiographic imaging as well as thin-cut high-resolution pelvic CT imaging upon presentation. Rapid limited-sequence MRI of the pelvis was obtained to evaluate for an occult femoral neck fracture. Results: Thirty-seven consecutive patients with 39 acute, high-energy femoral shaft fractures resulting from blunt trauma were included. The average age of the patients was 29.1 years (range, 14 to 82 years). Ten (25.6%) of the 39 femoral shaft fractures were open. Two femoral shaft fractures (5.1%) were associated with ipsilateral femoral neck fractures that were detected on radiographs, and no MRI was performed. None of the remaining 37 femoral shaft fractures were associated with a femoral neck fracture that was identified on CT imaging. Thirty-three (89.2%) of 37 patients underwent pelvic MRI to evaluate the ipsilateral femoral neck. Four (12.1%) of those 33 patients were diagnosed with a femoral neck fracture (2 complete, 2 incomplete) that was not identified on thin-cut high-resolution CT or radiographic imaging. Conclusions: Rapid limited-sequence MRI of the pelvis for patients with femoral shaft fractures identified femoral neck fractures that were not diagnosed on thin-cut high-resolution CT in 12% of our patients. Our results suggest that the frequency of femoral neck fractures may be underrepresented on CT imaging; rapid limited-sequence MRI was feasible without delaying definitive treatment even in polytraumatized patients. Level of Evidence: Diagnostic Level III . See Instructions for Authors for a complete description of levels of evidence.